An example on asymptotic on manifolds with corners - Harutyunyan, Gohar (Armenian Journal of Mathematics, 2010)
In this paper we consider an example on asymptotic expansions on manifolds with corner singularities. The content is a helpful step to understand how affects the push--forward operation under a $b$-fibration on the asymptotic data on basic objects, namely on $b$-densities.